Teaching Environmental Justice in the Framework for Education for Sustainable Development in College - María Martínez Lirola (Universidad Autónoma de Madrid, 2018)
One of the current challenges of higher education has to do with sustainability and environmental justice. For this reason, different activities related to sustainable education were designed so that college students could reflect on the importance of watching over the planet, fostering critical thinking and acquiring social skills that would be useful for the labor market, such as communication, cooperation or empathy. These activities were framed in a cooperative methodology so that students had to work in small groups to achieve a common goal. At the end of the semester an anonymous survey was prepared in order to know students' opinion about certain aspects related to sustainability and the different activities carried out. The results of the survey show that students consider important to introduce issues related to environmental justice in university education. They also note that they have learned vocabulary and aspects related to ecology and sustainability in carrying out the proposed activities in addition to acquiring the mentioned social skills.